Biochemical characterization of the bacterial peroxidase from the human pathogen Neisseria gonorrhoeae - Nóbrega, Cláudia S. (2022)
Fundacao para a Ciencia e a Tecnologia - PTDC/BIA-PRO/109796/2009 ; SFRH/BD/87878/2012 ; FCT/MEC - UID/Multi/04378/2013; ERDF - POCI-01-0145-FEDER-007728; Belgian Federal Science Policy Office (Belspo) - IAP7/44